The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.31744/einstein_journal/2021ao6027
|View full text |Cite
|
Sign up to set email alerts
|

Immediate analgesic effect of two modes of transcutaneous electrical nerve stimulation on patients with chronic low back pain: a randomized controlled trial

Abstract: Objective: To compare and assess the immediate analgesic effects of conventional and burst transcutaneous electrical nerve stimulation in patients with chronic low back pain. Methods: We conducted a three-arm single-blinded randomized controlled trial. A total of 105 patients with non-specific chronic low back pain aged between 18 and 85 years were randomly assigned into the following groups: Placebo Group (sham electrical stimulation), Conventional TENS Group (continuous stimulation at 100Hz for 100µs with se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 27 publications
(21 reference statements)
0
1
0
1
Order By: Relevance
“…Knowledge of cutaneous nerve topography can also be helpful in the application of noninvasive physiotherapy treatments in the case of low back pain. For instance, transcutaneous electrical nerve stimulation was proved effective for pain modulation [17]. Knowledge of lumbar dorsal rami may also be crucial for lumbar erector spinae plane block [6,8,9,11,14,18].…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge of cutaneous nerve topography can also be helpful in the application of noninvasive physiotherapy treatments in the case of low back pain. For instance, transcutaneous electrical nerve stimulation was proved effective for pain modulation [17]. Knowledge of lumbar dorsal rami may also be crucial for lumbar erector spinae plane block [6,8,9,11,14,18].…”
Section: Discussionmentioning
confidence: 99%
“…Já quando o modo aplicado consiste em baixa frequência o efeito desejado consiste na despolarização das fibras de dor rápida buscando, dessa forma, a ativação da analgesia por via descendente. Importante ressaltar, ainda, que independente do modo da EETN, quando o estímulo é aplicado, ocorre a ativação de receptores opioides no sistema nervoso central aumentando o limiar de dor e provocando uma maior analgesia (Pivovarsky et al, 2021;Calou et al, 2021).…”
Section: Terapia Não Farmacológicaunclassified
“…[10][11][12] Specifically, previous studies have shown that single and mainly combined use of transcutaneous electrical nerve stimulation (TENS), therapeutic ultrasound (US), massage, low-level laser, and exercise are effective not only in improving health and psychological status but also in alleviating pain severity and functional disability. [11][12][13][14][15][16][17][18] However, the clinical effect of the aforementioned intervention has not been documented beyond a reasonable doubt. In particular, a systematic review of eighty-three randomized controlled trials identified ambiguous evidence to support the effectiveness of conventional physical treatment for patients with CLBP, concluding that additional trials should be carried out to better comprehend and evaluate its efficacy.…”
Section: Introductionmentioning
confidence: 99%